Handbook of medical-surgical nursing - Mills, Elizabeth Jacqueline (Lippincott Williams & Wilkins, 2006)
Now in its updated Fourth Edition, this best-selling handbook is the most comprehensive pocket-sized guide to medical-surgical nursing. More than 300 disorders and treatments are covered in alphabetical order in a consistent quick-reference format, with icons, sidebars, alerts, illustrations, and tables to highlight key points. This edition covers bioterrorism-related disorders and new treatments such as enhanced external counterpulsation therapy and cardiac resynchronization therapy. A new icon highlights gender differences. Laboratory test results now include SI values. A new appendix on.